Ranking the socioeconomic and environmental framework of European Union farms: A network analysis - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
The context of European Union farms is markedly diverse. This is verified when, for example, several dimensions of the agricultural sector are analyzed, considering variables related with economic, social, or environmental dynamics. Indeed, frequently the farms in EU countries present relevant differences inside economic, social, or environmental dimensions. To better understand the interrelationships inside the economic, social, and environmental framework of European Union farms, this work analyzes the networks among these fields by considering rankings in decreasing order (with the statistical information of the representative farms of each European country) for variables like farming output, current subsidies, total inputs, gross investments, subsidies on investments, fertilizer and crop protection consumption, farming labor, and wages paid. Data was gathered from the Farm Accountancy Data Network, across the European Union member-states and over the period 2012-2014. This statistical information was analyzed through network analysis, exploring edgelists among the several variables considered and the network bridges between European countries. The results show that, in fact, there are significant differences in the scores found for European countries inside economic, social, and environmental dimensions, which was highlighted by the network analysis. However, the European Union farms are, in general, networked in the rankings for the variables considered.
Keywords: C45; D01; 330; European farm context; Edgelists and network bridges; Farm Accountancy Data Network; Benchmarking